Comparative efficacy and rankings of therapeutics for ALK-positive non-small cell lung cancer with brain metastasis: Updated results from a Bayesian network analysis based on randomized controlled trials. (May 2023) - Zhao, Binghao; Yao, Longping; Han, Yan; Qi, Hao; Wang, Yuekun; Xing, Hao; Ma, Wenbin
Graphical Abstract: ga1